Educação e transformação social: formas alternativas de educação em país descolonizado - Almeida, Hilda Maria Ferreira de (1981)
In this research work the compatibility between Guinea Bissau socioeconomic development model and her educational project is analysed. The country focused is an ex-portuguese colony in Africa that after independence has chosen an 'autonomous' way of development, which characterizes the 'social transformation' contexti an effort is made to be sure whether the present schoolsystem and government plans contribute to cut the links with pre-existent situation of dependency br noto The study starts wi th a general look onpre-colonial Africa and the difuse education which then existed, coming next a description of the Africa colonized by europeen countries and the characteristics of the school system adopted by the colonizers. Afterwards, Africa is studied from the period of the struggle for independence (in the sixties) until today, as well as the various socioeconanic , political and, particularly, educational op,!:ions adopted by the countries freed from colonial rule. Guinea Bissau is then analysed taking each historical period and making clear the connections between the dominant socioeconomic structure and governrnentpolicies regarding the education of the africans - pre-colonial Guineai the several stages of portuguese colonization (merchantilist periodi liberal portuguese monarchYi first stage of republican rulei Salazer dictatorship-before and after the guinean movement for independencei the struggle against the colonial rule until complete liberation of the country (1974). The third chapter analyses the period ~roffi those days onward until 1979 ('national reconstruction' stage).Several aspects of education are distinguished wi th the aim of comparing colonial stage with post-independence model: the links with productive activity, with social tasks and community lifei schooling prioritiesi urban and rural schools; school administration; tead'lers' qualification i educative methods, curricula and disciplines. The methodological approach is of ahistoricalstructural type. The existence of many material obstacles to the success of the guinean autonomous model must be mentioned. However,despite the surviving colonial characteristics , creative solutions are tried in education which favor independence, based on the priorities given by the population needs, the school's democratic administration , the integration wi th producti ve work and the 'africanization' of the courses.